AB0160 HDL Subclasses Concentration and Size Are Smaller in Systemic Lupus Erythematosus (SLE) and Are Not Modified During Sle Clinical Flares. (9th June 2015) - Nuria, A.; Parra, S.; Heras, M.; Canela, N.; Castro, A.; Correig, X.
Abstract : Background: A growing body of evidences reinforces the close link between systemic lupus erythematosus (SLE) and atherosclerosis which is due to traditional and non-traditional risk factors for cardiovascular diseases (CVD) that are overrepresented in SLE patients. Some studies have described a particular pattern of dyslipoproteinemia characterized by low HDL levels and increased triglycerides in SLE patients. Objectives: The aim of this study is to further characterize the HDL fraction of SLE and control patients, and to investigate whether the concentration and size of the main three HDL subclasses (large, medium and small HDL) of SLE patients are modified in a clinical flare. Methods: We studied a cohort of thirteen women with SLE and 13 age-matched population-based control women. (Lipids and apolipoprotein where measured using enzymatic and immunoturbidimetric assays. Total HDL was isolated from plasma using a sequential preparative ultracentrifugation.) Standard lipids where determined by classical biochemical methods and the concentration and the size of the three main HDL subclasses were determined by Nuclear Magnetic Resonance (NMR). Results: The SLE group presented a tendency to lower amount of triglycerides (TG) and esterified cholesterol (EC) carried by the large and medium HDL subclasses and a clear decrease up to 25% of the amount of TG and EC for the small HDL subclass (p=0, 03). The average size of each HDL subclass was slightly smaller in the SLE group. Both results were not different in presence of a clinical flare. Conclusions: The risk of the SLE patients to suffer a cardiovascular event is possibly increased due to a diminution of the HDL concentration and size, even during a period without a clinical flare. The capability of the HDL fraction in the reverse cholesterol efflux may possibly be compromised due to the changes in size and, consequently, in the HDL structure of the three subclasses. Disclosure of Interest: None declared